PENGARUH MODAL KERJA TERHADAP LABA BERSIH PADA PT. CAHAYA MURNI TIMUR JAYA DI JAYAPURA - Muhamad Syafii (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2017)
The purpose of this study was to determine the magnitude of the effect of working capital on net income. The results showed that the magnitude of the regression coefficient (r) indicates that the strength (strength) of a linear relationship and the direction of the relationship. If the correlation coefficient is positive, then the two variables have a unidirectional relationship. The results of the analysis show that the value of r = 0.703 which means that 70.3% of the working capital variable (X1) has a strong relationship to the net profit of the company. This means that the greater the working capital of a business/company, the greater the revenue from the net profit if all other indicators that support the revenue from the net profit are considered constant. Test the coefficient of determination (R2), this is indicated by R. Square = 0.494 or 94.4% which indicates that the variation of the independent variable (working capital) has a strong influence on the dependent variable. This means that R2 = 49.4% shows that the variation of the net income variable can be explained by the variation of the independent variables and the remaining 50.6% is influenced by other variables outside the variables that the authors examine. And the results of the t-test are to determine the t-table with a significance level of 0.05 or 95% confidence level where in the t-table the degrees of freedom = (nk) 5-1 = 4 so that df4 = 0.171 From the independent variable working capital so it appears that 1.711 > 0.171 with a significance level = 0.186. Thus, it means that H0 is accepted.